Fantos, Broquéis e a poesia nova de 1893 - Simões Júnior, Alvaro Santos [UNESP] (My University, 2013)
By the reading of news, reviews and essays published in Rio de Janeiro’s newspapers and periodicals, one intends to analyse how occured the perception and recognition of esthetic innovations introduced in Brazilian poetry by Fantos, by Lopes Filho, and Broquéis, by Cruz e Sousa.

A partir da leitura de notícias, resenhas e ensaios publicados na imprensa carioca no ano de 1893, analisa-se como se deu a percepção e o reconhecimento, por parte dos contemporâneos, das inovações estéticas introduzidas na poesia brasileira por Fantos, de Lopes Filho, e Broquéis, de Cruz e Sousa.
Keywords: Lopes Filho; Cruz e Sousa; Decadentism; Symbolism; Literary Criticism; Cruz e Sousa; Lopes Filho; Broquéis; Fantos; Decadentismo; Simbolismo